Damage Caused by Another in the Course of his Employment under the English and Bulgarian Tort Law - Tsoneva, Silvia (Yearbook of the Law Department, 2019)
This paper deals with the vicarious liability of one party held liable for the damage caused by another in the course of his employment under the English and Bulgarian tort law. The legal framework and caselaw on vicarious liability in the two legal systems are explored and analyzed in comparison.